Gender norms and intra-household allocation of labor in Mozambique: A CGE application to household economics - Diksha Arora; Codrina Rada (The University of Utah, Department of Economics, 2017)
We model intra-household dynamics in two rural provinces of Mozambique through the lens of computable general equilibrium (CGE) methods. The main features of the model are: 1) a household social accounting matrix that captures allocation of labor and resources, and transfers among household members; 2) the explicit use of social norms in labor allocation across gender; 3) a mechanism that links agricultural production to time poverty; and 4) the identification of leisure as a commodity that is being produced. Simulation results and sensitivity analyses show how social norms interact with the allocation of labor and resources at the household level to produce adverse results on farm production or limit the gains from technological improvements.
Keywords: D13; J22; Q12; 330; time poverty; gender; intra-household allocation; household accounting matrix; Mozambique